Meat for rooks: archaeology of the Francoist concentration camp of Casa del Guarda, 1938-1939 (Guadalajara, Spain) - Ruiz Casero, Luis A. (2023)
The following paper presents the results of the archaeological intervention, archival and oral sources research on one of the hundreds of imprisonment spaces of the Francoist dictatorship in Spain: the campo of Casa del Guarda, in Jadraque (province of Guadalajara). It served firstly as a forced labor camp during the Spanish Civil War, and later as a provisional concentration camp right at its end. In its final stage, it housed nearly five thousand prisoners from the disintegration of the armed forces of the Second Spanish Republic. This research made possible the reconstruction of the chronology and daily life of the inmates, to learn in detail their spatial distribution, to recover objects that belong to prisoners and guards, and to shed light on its history.